The Influence of Organizational Culture and Work Motivation on Organizational Commitment - Nur Syamsu; Jumiati Syam (Jurnal Economic Resource, 2021)
This study examines and analyzes the influence of organizational cultureand work motivation on organizational commitment at the Department ofWomen's Empowerment and Child Protection in the Mamasa Regency.Data collection using primary data with a questionnaire technique. Thepopulation in this study were all employees who worked at the Departmentof Women's Empowerment and Child Protection in Mamasa Regency. Asmany as 68 employees used a saturated sample so that 68 samples wereobtained. The questionnaire results have been tested for validity andreliability, as well as tested classical assumptions in the form of normalityassumptions and heteroscedasticity assumptions. Methods of data analysisusing multiple regression techniques. Based on the results of the analysis,it turns out that the research results prove that all hypotheses are acceptedbecause Organizational Culture and Work Motivation have a positive andsignificant effect partially and simultaneously on OrganizationalCommitment at the Department of Women's Empowerment and ChildProtection in the Mamasa Regency. It means that if employees canimprove their organizational culture and work motivation at work, theycan increase Organizational Commitment to the Office of Women'sEmpowerment and Child Protection in the Mamasa Regency.